The impact of Brexit on Francophone Africa - Kohnert, Dirk (My University, 2019)
Although Britain has been so far the hardest hit among the EU member states by the corona pandemic, Johnson persists to leave the EU at the end of 2020, whatever the cost. Presumably, the pandemic will have a by far bigger impact on the UK African trade than a no-deal Brexit. In Sub-Saharan Africa, South Africa had been arguably the hardest hit country both by Brexit and Corona. However, the poor, mainly working in the informal sector, were more concerned about the economic impact of the pandemic than the disease itself. In Nigeria, many people envisaged Corona as a plague of the rich and the elite. President Buhari shared the hubris of many British that they are less vulnerable to the pandemic and could continue with high-flying Post-Brexit plans. Ghana counts among those countries in Sub-Sahara Africa which has been most severely hit by the corona pandemic. But unlike South Africa and Nigeria, the direct effects of the pandemic on the downturn of its economy are not as significant as in other African states. In Kenya the number of corona-death had been much lower than for the SARS pandemic of 2003, but the transmission of the COVID-19 virus had been significantly greater. Nevertheless, many Kenyan’s saw the Brexit as a disguised blessing because they pined their hope on massive FDI by UK investors. In any case, it is clear beyond doubt that those who are to suffer most by the combined effects of the corona-pandemic and Brexit in Africa (and presumably world-wide) are the poor and needy
Keywords: Corona; Brexit; Africa; UK; EU; international trade; economic recession; poverty; South Africa; Nigeria; Ghana; Kenya